Using FRED data to teach price elasticity of demand. Issue 3 (3rd July 2017) - Méndez-Carbajo, Diego; Asarta, Carlos J.
ABSTRACT: In this article, the authors discuss the use of Federal Reserve Economic Data (FRED) statistics to teach the concept of price elasticity of demand in an introduction to economics course. By using real data in its computation, they argue that instructors can create a value-adding context for illustrating and applying a foundational concept in economics. Additionally, this pedagogical strategy contributes to developing an expected proficiency for economics majors related to "interpreting and manipulating data" (Hansen 2009, 2012). The authors provide step-by-step instructions on how to use FRED to compute the price elasticity of demand for motor vehicle fuels and gasoline as well as examples of in-class discussion questions and take-home assignments related to this instructional technique.